Land evaluation for land use planning in Sambhunath municipality of Saptari district, Nepal - Shrestha, Shobha; Karna, Bikash Kumar; Koirala, Hriday Lal (Geographical Journal of Nepal, 2022)
Dynamics of land use are closely related with society, development activities and environment. For the sustainable management of land resource of an area, land use may act as one of the elements of conflicts which could be resolved through land use planning ensuring equitable access and right of land to the owners. The present paper attempts to assess the land use for land use planning and infrastructure development through land evaluation including risk factors. Sambhunath municipality located within Saptari district of Nepal has been used as the study area to test the issues raised. Both qualitative and quantitative methods are used for data generation and analysis. Land use changes have been analyzed for the period 1986 to 2017. Potential land use zones have been identified through land suitability analysis using MCE-AHP and in relation to the risk factors such as flood, soil erosion, landslide, and fire. The infrastructure development plan has been allocated based on land use suitability index maps and planning guidelines. Land use projection have been made through Cellular Automata technique, and land use plans have been developed based on projected land use and optimized through SWOT analysis. Implementation strategy is developed based on legal framework to implement land use plan at local level. The land use change patterns are characterized by the increase of agriculture and built-up area and the decrease in areas under forest cover and water body simultaneously. Altogether 27 different criteria are identified and applied in land use suitability evaluation. Risk prone area is found mostly surrounding to the foot of Chure hill and along Khando river. Almost 46% of the total areas have been planned for future agriculture land use followed by residential, commercial, industrial and public uses which are 201 ha, 26 ha, 3ha, and 345 ha respectively. An implementation strategy has been devised to empower and enforcement for compliance of land use zone together with guidelines for outlined development activities.